EFEKTIFITAS MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP KETERAMPILAN BERHITUNG PECAHAN KELAS IVB MIN NGLAWU SUKOHARJO - Warsito, Warsito (UNIVERSITAS SLAMET RIYADI, 2019)
This study aims to determine: Effectiveness of the STAD type cooperative learning model on fraction counting skills in IVC class 2016/2017 academic year. This research is experimental research. with the design of the One Group Pretest Potest Design. The research sample was obtained from all class students of class IVB MIN Nglawu Sukoharjo totaling 38 students consisting of 23 male students and 15 female students .. The sampling technique in this study was total sampling. The technique of collecting data uses a fraction counting skill test. Test the validity of the data using the item analysis test using Anates. Data analysis techniques in this study are t-test and N-gain test. In this study analyzed with the help of SPSS 21 software t test and N-gain test.The result of calculating the value of